SNARE-Mediated Exocytosis in Neuronal Development - Urbina, Fabio L.; Gupton, Stephanie L. (Frontiers in Molecular Neuroscience, 2020)
The formation of the nervous system involves establishing a complex network of synaptic connections between proper partners. This developmental undertaking requires the rapid expansion of plasma membrane surface area as neurons grow and polarize, extending axons through the extracellular environment. Critical to the expansion of the plasma membrane and addition of plasma membrane material is exocytic vesicle fusion, a regulated mechanism driven by soluble N-ethylmaleimide-sensitive factor attachment proteins receptors (SNAREs). SNARE proteins bring two opposing membranes in close proximity and permit them to fuse, an essential task in eukaryotic cells. Since their discovery, SNAREs have been implicated in a number of critical neuronal functions involving exocytic fusion in addition to synaptic transmission, including neurite initiation and outgrowth, axon specification, axon extension, and synaptogenesis. The number and type of SNAREs critical at each stage of development varies, and decades of research have uncovered a rich variety of SNARE expression and function. The basis of SNARE-mediated fusion, the opening of a fusion pore, remains an enigmatic event, despite an incredible amount of research, as fusion is not only heterogeneous, but also spatially small and temporally fast. Early work led to controversies regarding the fate of the fusion pore after opening, and whether that be dilation or closure. Multiple modes of exocytosis have been proposed, with full-vesicle fusion (FVF) and kiss-and-run (KNR) being the best described. Whereas most in vitro work has reconstituted fusion using VAMP-2, SNAP-25, and syntaxin-1; there is much to learn regarding the behaviors of distinct SNARE complexes. In the past few years, robust heterogeneity in the kinetics and fate of the fusion pore that vary by cell type have been uncovered, suggesting a paradigm shift in how the modes of exocytosis are viewed is warranted. Here, we explore both classic and recent work uncovering the variety of SNAREs and their importance in the development of neurons, as well as historical and newly proposed modes of exocytosis, their regulation, and proteins involved in the regulation of fusion kinetics.